2023
DOI: 10.1002/brb3.2902
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 infection on cognition and its association with neurological symptoms

Abstract: Objective : To characterize the cognitive profile following COVID‐19 infection and its possible association to clinical symptoms, emotional disturbance, biomarkers, and disease severity. Methods : This was a single‐center cross‐sectional cohort study. Subjects between 20‐ and 60‐year old with confirmed COVID‐19 infection were included. Evaluation was performed between April 2020 and July 2021. Patients with previous cognitive impairment and other neurological or severe psychi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 57 publications
1
7
1
Order By: Relevance
“…Accordingly, examining the source variables results corrected for type I errors, our findings regarding ‘orthopedic disorders’ in males and ‘metabolic disorders’ and ‘physical health disparity’ in females were in agreement with those studies that observed deteriorated physical health in these areas in post-COVID19 patients (for reviews on orthopedic disorders see (Slouma, Abbes, Kharrat, & Gharsallah, 2022) and (Slouma et al, 2023) and for a review on metabolic disorders see (Steenblock et al, 2021). With regard to cognitive functions, our study’s findings on females’ reading time scores are consistent with earlier studies that have found an association between COVID-19 infection and impairment in information processing speed (Almeria, Cejudo, Sanz-Santos, Deus, & Krupinski, 2023; Ferrucci et al, 2021; Flegr & Latifi, 2023). However, unlike these studies, we found a significant negative correlation between COVID-19 infection and females’ reaction times in the Stroop test, indicating improved reaction times compared to those who were not infected.…”
Section: Discussionsupporting
confidence: 92%
“…Accordingly, examining the source variables results corrected for type I errors, our findings regarding ‘orthopedic disorders’ in males and ‘metabolic disorders’ and ‘physical health disparity’ in females were in agreement with those studies that observed deteriorated physical health in these areas in post-COVID19 patients (for reviews on orthopedic disorders see (Slouma, Abbes, Kharrat, & Gharsallah, 2022) and (Slouma et al, 2023) and for a review on metabolic disorders see (Steenblock et al, 2021). With regard to cognitive functions, our study’s findings on females’ reading time scores are consistent with earlier studies that have found an association between COVID-19 infection and impairment in information processing speed (Almeria, Cejudo, Sanz-Santos, Deus, & Krupinski, 2023; Ferrucci et al, 2021; Flegr & Latifi, 2023). However, unlike these studies, we found a significant negative correlation between COVID-19 infection and females’ reaction times in the Stroop test, indicating improved reaction times compared to those who were not infected.…”
Section: Discussionsupporting
confidence: 92%
“…We did not find an association between the severity of the disease and a worse neurocognitive performance. Other studies have also indicated no link between the disease’s severity and neuropsychological performance [ 10 , 37 , 38 , 39 , 40 , 41 , 42 ]. No neuropsychological differences were observed between the four groups considering severity, indicating that an association between disease severity and neurocognitive performance cannot be established.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [ 5 , 10 , 38 ] have pointed out that neurological symptoms at the onset of the disease may be associated with a lower neurocognitive performance. We evaluated whether presenting with neurological symptoms in the acute phase of the disease had an impact on neuropsychology at 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations